Students’ Writing Quality: Its Coherence and Cohesion - Farida, Alief Noor; Rosyidi, Mohamad Ikhwan (Universitas Negeri Semarang, 2019)
Students’ writing quality has become the focus of education research nowadays. A good quality writing should fulfil the requirements of coherence and cohesion. Coherence shows how the sentences in the text are arranged which usually follow certain structure, and cohesion shows how they are connected to each other. This study aims to investigate the students’ writing quality in both aspects. Using systemic functional linguistics approach, 10 students’ writing on recount text is analysed. The result of the study reveals how good the students on the fourth semester can write the text and what devices they use to establish the quality. The students can follow the generic structure of recount texts well. However, only 50% has reorientation. In addition, they employ different thematic progressions,